2014
DOI: 10.21273/horttech.24.6.676
|View full text |Cite
|
Sign up to set email alerts
|

Refining Postharvest Handling Procedures Increased Cut Rose Vase Life

Abstract: ADDITIONAL INDEX WORDS. Rosa hybrida, 1-methylcyclopropene, ethylene, silver thiosulfate, senescence SUMMARY. Various postharvest procedures were conducted on several rose (Rosa hybrida) cultivars to determine the effects on vase life, water uptake, change in fresh weight, stage of opening, and vase life termination criteria. Vase life was influenced by cultivar and vase solution. Commercial preservative solutions resulted in a longer vase life, smaller decrease in fresh weight than the controls, and smaller i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Improving water uptake of cut flowers during the vase life have been reported by various researchers which is in line with the findings of the present study (Singh et al, 2004;Marandi et al, 2011;Moody et al, 2014). The results can be associated with the biocide effects of both chemicals.…”
Section: Postharvest Physiology As Affected By Pulsing Preservative Asupporting
confidence: 93%
See 1 more Smart Citation
“…Improving water uptake of cut flowers during the vase life have been reported by various researchers which is in line with the findings of the present study (Singh et al, 2004;Marandi et al, 2011;Moody et al, 2014). The results can be associated with the biocide effects of both chemicals.…”
Section: Postharvest Physiology As Affected By Pulsing Preservative Asupporting
confidence: 93%
“…In agreement with these findings, effective transportation of water within the floral stems and reduced stem blockage were also observed by various researches in different cut flowers . The different repose of rose varieties to the pulsing preservatives indicated in the present study is may be associated with the genetic makeup of the varieties (Moody et al, 2014) where the variety Athena could be more responsive to STS than the varieties Moon Walk and Upper Class do.…”
Section: Postharvest Physiology As Affected By Pulsing Preservative Amentioning
confidence: 66%
“…'Freedom' roses remained alive the longest in phenolformaldehyde foam (average, 9.5 d) compared with basalt floral fiber (average, 8.8 d) and coir pouches (average, 6.6 d). Previous research found 'Freedom' roses to have an average vase life of 8.5 to 13.1 d in water free of floral preservatives (Moody et al 2014;Ranwala 2022). As the expected vase life by most customers is 7 d, both the phenol-formaldehyde foam and basalt fiber foam were found to be adequate media for use in retail floral arrangements in which roses are used (Ranwala 2009).…”
Section: Resultsmentioning
confidence: 97%
“…However, stem collapse occurred significantly more often (P < 0.001) when stored at À0.6 C than when stored at 4 C for all storage durations, and significantly less (P # 0.01) when pulsed with C100 before extended storage rather than C200. This could also be attributable to the lack of adequate hydration prestorage with C200 caused by carbohydrates restricting adequate flow of water uptake (Marousky 1971;Moody et al 2014). Stem collapse was only significant in Expt.…”
Section: Discussionmentioning
confidence: 99%